Efficacy of Different Sampling Methods of Sand Flies (Diptera: Psychodidae) in Endemic Focus of Cutaneous Leishmaniasis in Kashan District, Isfahan Province, Iran. - Marzieh Hesam-Mohammadi; Yavar Rassi; Mohammad Reza Abai; Amir Ahmad Akhavan; Fatemeh Karimi; Sina Rafizadeh; Alireza Sanei-Dehkordi; Maryam Sharafkhah (Tehran University of Medical Sciences, 2014)
Background: The aim of the study was to evaluate and compare the efficiency and practicality of seven trappingmethods for adult phlebotominae sand flies. The results of this investigation provide information to determine the species composition and nocturnal activity pattern of different sand fly species. Methods: The study was carried out in both plain region (about 5km far from northeast) and mountainous region (about 40km far from southwest of Kashan City). Seven traps were selected as sampling methods and sand flies were collected during 5 interval times starting July to September 2011 and from 8:00PM to 6:00AM in outdoors habitats. The traps include: sticky traps (4 papers for 2 hours), Disney trap, Malaise, CDC and CO2  light traps, Shannon traps (black and white nets) and animal-baited trap. Results: A total of 1445 sand flies belonging to 15 species of Phlebotomus spp. and five of Sergentomyia spp. were collected. Females and males comprised 44.91% and 55.09% of catches, respectively. Of the collected specimens, Se. sintoni was found to be the most prevalent (37.86%) species, while Ph. papatasi, accounted for 31.76% of the sand flies. Conclusion: Disney trap and sticky traps exhibited the most productivity than other traps. In addition, in terms of the efficiency of sampling method, these two trapping methods appeared to be  the most productive for both estimating the number of sand flies and the species composition in the study area.